PRINSIP KETERBUKAAN INFORMASI (FULL DISCLOSURE) DALAM PROSES IPO PADA MASA PANDEMI COVID-19 - Amiruddin, Nanda Vita Reka; Soefyanto, Soefyanto; Umam, Irfan Khairul (JOURNAL of LEGAL RESEARCH, 2023)
The background of this research issue is based on the importance of information disclosure to companies that conduct public offerings in the capital market as a determinant for investors to make decisions because the Covid-19 pandemic is one of the extraordinary events that greatly affect several sectors, one of which is in the capital market. This thesis aims to review the fulfillment of the principle of information disclosure in the IPO (Initial Public Offering) process during the Covid-19 pandemic. This research is library research, examines the momentum that is happening at this time and relates the prevailing laws and regulations to support research. The analysis method used is normative juridical by using statute approach, as well as conceptual approach. In this study using three main legal materials used, namely, the primary legal material consists of Law No. 8 of 1995 on Capital Market, Law No. 8 of 1995 on Capital Market, Law No. 21 of 2011 on Financial Services Authority, and Bapepam Regulation Number IX.A.2 on Registration Procedures in the Framework of Public Offerings. The results showed that OJK issued several regulations for the capital market sector due to the Covid-19 pandemic that had an impact on companies and investors, but OJK has not issued specific regulations for the application of information disclosure principles in the IPO process during the pandemic so that there are still existing regulations related.